An experimental study on the anisotropic and intermittent behaviour of a turbulent flow over a rough bed. Issue 1 (1st June 2022) - Coscarella, F; Penna, N; Servidio, S; Gaudio, R
Abstract: The flow field in open channels can be classified into different zones according to the velocity distribution. To explore the anisotropic and intermittent behaviour in the turbulent flow layers, an experimental study was performed using Particle Image Velocimetry (PIV) measurements in a hydraulic flume with rough bed. Specifically, the analysis has been focused on the two-dimensional (2D) high-order structure functions applied to the velocity data. It is demonstrated that the system spans from large-scale anisotropy, which is induced by the main shear of the boundary layer, to small-scale isotropy. Moreover, it is shown that the intermittency is more pronounced in the near-bed layer, where the flow is more populated by coherent whirling structures. In essence, both anisotropy and intermittency are proved to be important phenomena for natural bed rivers, since they affect the turbulence transport characteristics of the flow.